The Effect of using Community Language Learning Method to Improve Students’ Speaking Ability - S Syamsia; Hatima Kaunar (Jurnal Langua, 2020)
This research was conducted to know the effectiveness of using the community language learning method (CLLM) is to improve speaking ability. The significance of this research can improve students speaking ability in used community language learning methods to teach speaking. It can be proved from the t-test, and then based on the analysis data of result students worked value lower than 75.77 for level significance 78.85, so there are differences speaking achievement between experiment and control class. The students who are taught by using the community language learning method have a higher score than those are taught by using CLLM. The result of the data analysis proven than student’s score of speaking taught by using community language learning is better. It means that the use of community language learning method to teach speaking is quite effective.